A comprehensive urinary steroid analysis strategy using two-dimensional gas chromatography – time of flight mass spectrometry. Issue 18 (29th August 2018) - Bileck, Andrea; Verouti, Sophia N.; Escher, Genevieve; Vogt, Bruno; Groessl, Michael
Abstract : Steroids are key players in a high variety of physiological processes and are typically analyzed for the diagnosis of hormonal disorders. Abstract : Steroids are key players in a high variety of physiological processes and are typically analyzed for the diagnosis of hormonal disorders. Due to their chemical and structural similarity many of these metabolites cannot be separated by conventional techniques such as liquid chromatography. Herein, we present an analysis strategy based on two dimensional gas chromatography (GC×GC) coupled to time-of-flight mass spectrometry (TOF MS) which demonstrates superior separation power and enables comprehensive screening of steroids. We show absolute quantitation of 40 steroids in human urine over three orders of magnitude with limits of detection ≤50 nM and the tentative identification of additional 30 steroids based on accurate mass, isotopic pattern analysis and spectral similarity matching to known steroids. The method displays excellent inter- and intra-day stability, repeatability and recovery and was validated for clinical routine analysis. Additionally, we demonstrate the potential of the approach for untargeted analysis of urinary steroids in mouse and rat.